PROSECUTOR’S SUPERVISION DOCUMENTS IN ENSURING THE LEGALITY OF DECISIONS OF LOCAL REPRESENTATIVE AND EXECUTIVE AUTHORITIES - Oybek Shokirov (Scholar Express Journals, 2025)
The article provides a scientific analysis of the role and significance of prosecutorial supervision in ensuring the legality of decisions adopted by local representative and executive authorities. The author examines the activities of the prosecution bodies in connection with the mechanisms of upholding the rule of law enshrined in Articles 143-145 of the Constitution. The types of prosecutorial documents, their adoption and implementation procedures, as well as the legal basis for their application, are discussed in detail. The paper also highlights the necessary conditions for enhancing the effectiveness of prosecutorial measures. Through examples from current practices, the author illustrates the importance of prosecutorial supervision in preventing legal violations committed by local authorities, particularly in the field of land relations. The article further explores the prosecutorial role in safeguarding citizens’ rights and legitimate interests through judicial intervention. In conclusion, the author proposes several scientific and practical recommendations, including the mandatory participation of prosecutors in administrative cases related to land disputes, the adoption of a Supreme Court Plenary Resolution on the uniform application of legislation, and the introduction of electronic information exchange among state institutions. The results of the research contribute to improving the effectiveness of prosecutorial activities and ensuring the supremacy of law.
Keywords: Prosecutorial supervision; legality; local authorities; prosecutorial documents